2018
DOI: 10.3390/ijgi7030100
|View full text |Cite
|
Sign up to set email alerts
|

Do Charitable Foundations Spend Money Where People Need It Most? A Spatial Analysis of China

Abstract: Charitable foundations are a critical part of public services. However, there is a large gap between the locations and expenditures of charitable foundations and the real population needs for most nations. Three types of Chinese local charity foundations, i.e., those for poverty, education and medical assistance, are used as examples to explore the distinct gaps. The spatial distributions of local charity foundations are characterized by spatial scan statistics and spatial autocorrelation models. The local pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…From this perspective, the operators would become an extension of the State and implement a diversity of actions and strategies such as PPANs; likewise, a comprehensive menu of entities with interference in the entire spectrum of policies would proliferate, from their design, including their implementation and evaluation. Several authors analyze how non-governmental entities play an active role in implementing social policies, particularly those of health and nutrition, not only in Latin America but also in other continents such as Africa and Asia [32][33][34][35][36] . During the development period of this research, some complaints about severe irregularities in child care by private operators were made, which showed that said entities had found a source of enrichment in the programs' operation while not complying with the function for which they were recruited.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, the operators would become an extension of the State and implement a diversity of actions and strategies such as PPANs; likewise, a comprehensive menu of entities with interference in the entire spectrum of policies would proliferate, from their design, including their implementation and evaluation. Several authors analyze how non-governmental entities play an active role in implementing social policies, particularly those of health and nutrition, not only in Latin America but also in other continents such as Africa and Asia [32][33][34][35][36] . During the development period of this research, some complaints about severe irregularities in child care by private operators were made, which showed that said entities had found a source of enrichment in the programs' operation while not complying with the function for which they were recruited.…”
Section: Discussionmentioning
confidence: 99%
“…As analyzed in Figure 3, a large number of SDG targets can be directly or indirectly achieved by improving population accessibility to facilities through transport. Earth observation for more efficient and accurate modeling have been applied in improving the provision of urban green space for residents [192], minimizing urban-rural inequality in accessing public facilities [53,71], engaging rural and remote residents to work to decrease poverty incidences and achieve gender equality [1,193,194], etc. In addition, land, climate and environmental factors of infrastructure performance have been derived from Earth observation to estimate risks, disasters and future scenarios of performance [195,196].…”
Section: Typical Cases Of Eosimentioning
confidence: 99%